Derivation of Huntington Disease affected Genea090 human embryonic stem cell line - Biljana Dumevska; Julia Schaft; Robert McKernan; Jesselyn Hu; Uli Schmidt (Stem Cell Research, 2016)
The Genea090 human embryonic stem cell line was derived from a donated, fully commercially consented ART blastocyst, carrying Htt gene CAG expansion of 45 repeats, indicative of Huntington Disease. Following ICM outgrowth on inactivated human feeders, karyotype was confirmed as 46, XX by CGH and STR analysis demonstrated a female allele pattern. The hESC line had pluripotent cell morphology, 91% of cells expressed Nanog, 95% Oct4, 90% Tra1–60 and 100% SSEA4 and gave a pluritest pluripotency score of 30.91, novelty of 1.23. The cell line was negative for Mycoplasma and visible contamination.